Health Problem Related Smoking Behaviour Among Adult in Indonesia - Nian Afrian Nuari (STIKes Patria Husada Blitar, 2020)
Smoking behaviour is a problem that is often found in Indonesian society. The number of active smokers in Indonesia is increasing from year to year. Smoking can cause losses both in terms of socio-economic and health and even death. The aim this research is (1) to assess the prevalence of smoking cigarette among adult in Indonesia, and (2) to analizing relationship between health problem and smoking cigarette among adult in Indonesia. This is a cross-sectional study based on data extracted from the Indonesia Demographic and Health Survey, 2017. A household-based survey, implemented in a representative probability sample of more than 47963 households from urban and rural areas in Indonesia. This research was analytic correlational study with Cross sectional approach. The sample of reserach were 18023 adult aged between 15 and 44 years. Relationship between health problem and smoking cigarette among adult in Indonesia was assessed by bivariate methods. Based on the results of the study found that most smokers have ages, residing in rural areas, secondary level education background, have a very poor wealth index level. The research findings found there is a relationship between age (p=0,001), type of residence (p=0,005), type of education (p=0,000), type of wealth index (p=0,000), and health problem related smoking behavior. The findings indicate that there is a relationship between complaints of short / rapid breath (p=0,001), and dont have relationship with nasal disorders and the presence or absence of cough with smoking behavior.